2020
DOI: 10.1002/adtp.201900182
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy of Myocardial Infarction: A Promising Opportunity in Bioengineering

Abstract: Myocardial infarction (MI) is a life‐threatening disease resulting from the irreversible death of cardiomyocytes (CMs). Stem cell‐based therapies have been studied for MI treatment over the last two decades with promising outcomes. Here, the past work in this field is critically reviewed to elucidate the advantages and disadvantages of treating MI using pluripotent stem cells (PSCs) including both embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSCs), adult stem cells, and cardiac progenitor c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 298 publications
(333 reference statements)
0
11
0
Order By: Relevance
“…Instead, this scenario argues for the paracrine effects described for these cells in multiple reports (Nascimento et al, 2014 ; Yao et al, 2015 ; Cai et al, 2016 ) in which immunomodulatory properties, ECM remodeling ability and capacity to promote angiogenesis are the main mechanisms (Guo et al, 2020 ). Several bioengineering strategies are under development to improve retention, survival, and engraftment of transplanted cells in the myocardium (Jiang et al, 2020 ). Of interest, a recently developed hydrogel-based combination of UCM-MSC with endothelial cells showed that in vitro maturation prior to transplantation promotes vasculogenic potential and cell survival/retention after transplantation in mice (Torres et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Instead, this scenario argues for the paracrine effects described for these cells in multiple reports (Nascimento et al, 2014 ; Yao et al, 2015 ; Cai et al, 2016 ) in which immunomodulatory properties, ECM remodeling ability and capacity to promote angiogenesis are the main mechanisms (Guo et al, 2020 ). Several bioengineering strategies are under development to improve retention, survival, and engraftment of transplanted cells in the myocardium (Jiang et al, 2020 ). Of interest, a recently developed hydrogel-based combination of UCM-MSC with endothelial cells showed that in vitro maturation prior to transplantation promotes vasculogenic potential and cell survival/retention after transplantation in mice (Torres et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…This means the human iPSC may still possess some of the phenotypic properties of the more differentiated cells from which they are reprogrammed, leading to less potent potential of differentiation of human iPSCs than human ESCs [ 59 , 61 ]. Therefore, protocols of cardiac differentiation for human ESCs may not work well for human iPSCs and usually have an OBT ranging over ~7 days [ 31 , 62 , 63 ]. This is consistent with our observation that cardiac differentiation of the human eiPSCs and IMR90-1 iPSCs cultured in 3D with the commonly used RI concentration (10 μM) results in significantly heterogeneous cell populations and compromises the efficiency of cardiac differentiation, although the high concentration of RI has been used to culture human ESCs for cardiac differentiation (mostly under 2D) with high efficiency (the cTnT-positive cells may be up to 90 %) [ 26 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, these protocols are lengthy (typically requiring at least 14 days) and generate CSs with high heterogeneity [ [28] , [29] , [30] ]. The latter is evidently reflected by the large variation of the outset beating time (OBT) of the CSs, which is typically over ~7 or more days for all contemporary 3D cardiac differentiation approaches [ 21 , 31 ]. The OBT is a direct indicator of the maturity of the PSC-derived CSs because their beating is a result of the maturation of the intra- and inter-cellular protein system that drives the motion.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al, bioengineered an injectable nanomatrix gel containing an amphiphilic peptide and a cell adhesive ligand Arg-Gly-Asp-Ser (PA-RGDS). Upon evaluation of the therapeutic potential and long-term effect of the suspension of mouse embryonic stem cells (mESCs)-derived cardiomyocytes for engraftment in an MI rat model, their results showed retention of engrafted cardiomyocytes for up to 3 months and improved function of the heart post-administration [ 68 ].…”
Section: Mechanics Of Microencapsulationmentioning
confidence: 99%